Effects of seeding method, spacing and fertilizer on Chinese kale (Brassica alboglabra) - Choo, Wong Kai; Kee, Lee Eng (Faculty of Agriculture, University of Malaya, 1974)
Two seeding methods, three spacings within 30 cm row and three forms of fertilizer were investigated on Chinese kale ('Kai Lan') in a factorial experiment. Transplanting at 2 weeks after sowing resulted in more vigorous plant growth and higher marketable fresh-weiqnt yield with greater mineral content than direct seeding. Decreasing plant spacing within the row from 30 cm to 20 cm and 10 cm resulted in a progressive increase in fresh-weight yield per hectare, due mainly to a greater number of plants per hectare. A combination, of cowdung and inorganic fertilizer was superior to inorganic fertilizer alone which in turn was superior to a commercial organic-inorganic fertilizer mixuture.